FREQUENT USERS OF EMERGENCY DEPARTMENTS IN TIRANA REGION DURING PANDEMIC - Edmond ZAIMI; Artur XHUMARI; Elisabeta OSMANAJ; Paolo CONTINI; Lucia MONACIS; Elizana PETRELA (Anthropological Researches and Studies)
Objectives. Being given the limited studies on the flow of patients in Albanian emergency departments (EDs), this study made the profile of the frequent patients who attended EDs during the pandemic. This article aimed to evaluate the weight and the factors which accompanied the frequent ED users even in some unusual situations.